Eight Days to Live - Johansen, Iris (New York : St. Martins Press, 2010)
Eve Duncans adopted daughter Jane has been targeted by a mysterious cult who has decided that she has only eight days to live.
Keywords: Duncan, Eve -- (Fictitious character) -- Fiction; Artists -- Fiction; Painting -- Fiction; Cults -- Fiction; Human sacrifice -- Fiction; Fiction